Moving from Knowledge to Action: A Qualitative Study of Elite Coaches' Capacity for Early Intervention in Cases of Eating Disorders - Nowicka, P.; Eli, K.; Ng, J.; Apitzsch, E.; Sundgot-Borgen, J. (International Journal of Sports Science and Coaching, 2013)
This study investigates elite coaches' attitudes toward eating disorders (ED), knowledge about ED, and early intervention skills when confronted with possible ED in their female athletes. We interviewed 18 coaches in Sweden responsible for athletes representing national teams in the three sports categories most at risk for ED: aesthetic, weight class, and endurance. The interviews revealed that, although most coaches knew athletes with ED, they did not perceive ED as a problem in their sport. The majority of coaches cited difficulties in identifying ED symptoms, especially symptoms associated with bulimia nervosa. Coaches also described several barriers in approaching the athletes, including the athletes' denial of ED, lack of female colleagues on the team and the lack of easily accessible resources for treatment referral on both the national sports federation and the club levels. This study reveals that elite coaches have insufficient capacity to identify ED and conduct early intervention, resulting in delayed treatment.